Malaysia identity for or against the multiracial and multi-ethnic society - Zaaba, Zuraidah; Jalil, Saiful Zizi; Gunggut, Haijon; Thomas, Bibianah (Faculty of Administrative Science and Policy Studies, 2023)
After 57 years of Malaysia's independence, the identity of races and ethnicity are still explicitly prevailed in politics, education, and economic domains. This is reminiscent of the British divide and rule policy during it colonised Malaya and North Borneo. The division in society is prevailing in education and economic and economic context. The aim is to explore whether the division leads to dynamic or destruction in Malaysian society. Hence, this article focused on multiracial society and multi-ethnic society in economics context, education context and politics explained through historical context. Initially, this paper elaborated British colonisation divide and rule policy. There was a division in society especially in politics, education, and economic sectors. This impact on preserving the status quo of each of the main races and ethnicities was to be identified with their various economic activities. However, towards the process of independence of Malaya 1957, the three races formed Alliance party comprised of United Malay National Organisation (UMNO), Malayan Chinese Association (MCA), and Malayan Indian Association (MIC) to gain independence. Later, the Alliance party and political parties in Sabah and Sarawak united to gain independence from Malaysia in 1963. In addition, there are explorations of areas i.e. economic, education and language and premiership and Islam that influence the development of Malaysian identity. The later part of the paper explored the scenario of Malaysian society towards the year 2020. The findings so far, Malay and Bumiputera Sabah and Sarawak rights still explicitly/implicitly in all government policies. There are vernacular schools along with national schools. The Chinese monopolise the economic sector. The Indians and minorities are considered unrepresentative in all sectors. However, when Malaysians are at threat of destruction as a result of corruption and integrity in the government; Malaysian society united again through Pakatan Harapan (PH)( comprised of Parti Pribumi, Amanah, DAP, PKR, WARISAN, and Sarawak main political parties) for 2018 general election(GE). The development in Malaysian society after PH won GE 2018 was to acknowledge all races and ethnicity; as well as attempt to address all issues. Unfortunately, PH short live with incompatibility among coalition parties led to Malay supremacy reinstate in March 2020. Despite the change of government, there is evidence of a trend leaning towards dynamic in Malaysian society to overcome pandemic Covid-19 in 2020 and 2021.